Chương 3: NGUYÊN HÀM. TÍCH PHÂN VÀ ỨNG DỤNG

Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Akai Haruma
30 tháng 11 2021 lúc 22:48

Lời giải:
\(I=\int ^1_{-1}\frac{1}{(2-x)(2+x)}dx=\frac{1}{4}\int ^1_{-1}(\frac{1}{2-x}+\frac{1}{2+x})dx\)

\(=\frac{1}{4}\int ^1_{-1}\frac{1}{2-x}dx+\frac{1}{4}\int ^1_{-1}\frac{1}{2+x}dx\)

\(=\frac{-1}{4}\int ^1_{-1}\frac{1}{x-2}dx+\frac{1}{4}\int ^1_{-1}\frac{1}{x+2}dx\)

\(=(-\frac{1}{4}\ln |x-2|+\frac{1}{4}\ln |x+2|)^1_{-1}=\frac{1}{2}\ln 3\)


Các câu hỏi tương tự
Luân Trần
Xem chi tiết
Lan Hương
Xem chi tiết
Shuu
Xem chi tiết
Kim Tuyền
Xem chi tiết
Phùng Lâm
Xem chi tiết
Phương Anh
Xem chi tiết
Tuyết Minh
Xem chi tiết
Nguyễn Thái Quân
Xem chi tiết
Phạm Thị Thúy Giang
Xem chi tiết
Bùi Chí Trung
Xem chi tiết